Pengaruh Budaya Organisasi Terhadap Turnover Intention Pada Protech Dry Cleaning & Laundry Makassar - Musa, Chalid Imran; Tawe, Amiruddin (CV. Lafadz Jaya, 2023)
The purpose of the study was to determine the effect of the influence of organisational culture on turnover intention at Protech Dry Cleaning & Laundry Makassar. The population in this study were all employees of Protech Dry Cleaning & Laundry Makassar. sampling in this study was carried out using the census technique so that 83 respondents were sampled. The type of research used is quantitative. The data used is primary data obtained by distributing questionnaires to employees. The data analysis method uses simple linear regression. The results of the study that organisational commitment partially has a significant effect on turnover intention. This is evidenced by organisational culture (X) showing a tcount value of 3.711. In addition, the significance value (Sig.) is 0.003. This result shows that the tcount value is greater than the ttable value (3.462> 1.98932) and the significance value is less than 0.05 (0.001 <0.05). The Adjusted R square result is 0.526, which indicates that 52.6% of the variability of turnover intention can be explained by the aggregate effect of the Organisational Culture variable. The remaining variability of 47.4% is due to other variables not observed within the scope of this study.